The effectivity of problem-based learning to improve the HOTS: A meta-analysis - Risqi Utami; Azma Rosyida; Janu Arlinwibowo; Gupita Nadindra Fatima (Psychology, Evaluation, and Technology in Educational Research, 2022)
This study aims to determine the effect of problem-based learning on higher-order thinking skills (HOTS) through meta-analysis. Data is collected by research documentation generated from various sources collected through the Internet. These articles were published from 2019 to 2022. The themes discussed the effect of PBL to HOTS on students' skill abilities, analysed quantitatively, described data in sample sizes, standard deviations, and averages, and published in journals and indexed on Google Scholar. The analysis design used a contrast group with a random effects model that corrected for effect sizes. The analysis used JASP software to calculate mean aggregate differences, plot forest plots, and publication bias. The study results show a significant difference between groups using control and experimental in the learning process (SE = 1.00); students who use PBL in learning have better learning outcomes than those who do use conventional. Based on the analysis results, the urgency of implementing PBL is evident in supporting the problem-based learning process with HOTS skills.